TEN CONSIDERATIONS IN THE DEVELOPMENT OF THE FINANCIAL THERAPY PROFESSION - Jerry Gale; Joseph Goetz; Sonya Britt (Journal of Financial Therapy, 2012)
The purpose of this paper is to serve as a primer for considerations and conversations that will need to take place to continue, and potentially even expedite, the positive evolution of the relatively new concept of financial therapy and the newly formed Financial Therapy Association (FTA). Varying perspectives are provided by reviewing other associations’ challenges when implementing cross-disciplinary collaboration. Ten considerations are provided for those interested in the development of financial therapy, which are designed to be referenced on an ongoing basis to facilitate the strong development of this new discipline and association. Exercises are provided to assist professionals in recognizing similarities and differences between their profession and others represented in the membership of FTA.
Keywords: financial therapy; financial planning; financial counseling; marriage and family therapy, psychology, social work